Arbuscular mycorrhizal symbiosis of herbaceous invasive neophytes in the Czech Republic - Štajerová, Kateřina (Jihočeská univerzita, 2009)
I have studied arbuscular mycorrhizal symbiosis of 44 herbaceous invasive neophytes occuring in the Czech Republic. My results show that about 70% of the examined species are capable to form symbiotic association with arbuscular mycorrhizal fungi (AMF) in the field. To my knowledge, mycorrhizal status of 23 invasive species is reported here for the first time. I predicted, based on the hypothesis of Urcelay & Díaz (2003), that the intensity of AMF in the roots of invasive species will be correlated with that of the native dominant species of invaded plant community, but collected data did not support this hypothesis. In addition, the effects of habitat and community characteristics on the intensity of AMF colonization of the invasive species’ roots were tested. My results show that, at the within-species level, plants in the habitats with higher light and temperature conditions have less colonized roots whereas intensity of mycorrhizal colonization increases with habitat moisture. At the among-species level, invasive species occurring in the habitats with elevated nitrogen availability have higher mycorrhizal colonization of their roots. The effect of nitrogen availability is revealed at the among-species level and stays significant even after phylogenetic correction, suggesting this is an evolutionary adaptation rather than a phenotypic plasticity.
Arbuscular mycorrhizal symbiosis of herbaceous invasive neophytes in the Czech Republic
Keywords: alien; arbuscular mycorrhiza; community; dominant species; habitat; light; moisture; mycorrhizal status; nitrogen; non-native; temperature; alien; arbuscular mycorrhiza; community; dominant species; habitat; light; moisture; mycorrhizal status; nitrogen; non-native; temperature